Authenticated file broadcast protocol - Reis, Simão (2015)
The File Broadcast Protocol (FBP) was developed as a part of the DETIboot system. DETIboot allows a host to broadcast an operating system image through an 802.11 wireless network to an arbitrary number of receivers. Receivers can load the image and immediately boot a Linux live session. The initial version of FBP had no security mechanisms. In this paper we present an authentication protocol developed for FBP that ensures a correct file distribution from the intended source to the receivers. The performance valuations have shown that, with the best operational configuration tested, the file download time is increased by less than 5%.